Role of structural distortion in stabilizing electrosynthesized blue emitting phosphorene quantum dots - Valappil, Manila Ozhukil; Joshi, Krati; John, Lisa; Krishnamurthy, Sailaja; Jana, Bikash; Patra, Amitava; Pillai, Vijayamohanan K.; Alwarappan, Subbiah (Journal of Physical Chemistry Letters, 2019)
Luminescent phosphorene quantum dots (PQDs) have emerged as fascinating nanomaterials for potential applications in optoelectronics, catalysis, and sensing. Herein, we investigate the structural distortion of black phosphorus (BP) under an applied electric field to yield blue luminescent PQDs [average diameter 8 +/- 1.5 nm (N = 60)]. The electrosynthesized PQDs exhibit photoluminescence emission independent of excitation wavelength with 84% quantum efficiency. Structural distortion that occurred during the transformation of BP to PQDs is confirmed by results obtained during transmission electron microscopy, X-ray diffraction and X-ray photoelectron spectroscopy. Further, using first-principles-based density functional theory, calculations on oxygenated and nonoxygenated PQDs augment the experimental observations that an optimum oxygen content maintains the structural integrity of PQDs, above which the structural robustness of PQDs is drastically diminished.